2021
DOI: 10.3390/su13179768
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Education with Mobile Learning for English for Specific Purposes (ESP): A Systematic Review (2012–2021)

Abstract: Mobile learning for English Language Teaching (ELT) has become an emerging trend to sustain education, providing the option to learn English for Specific Purposes (ESP). However, the review of mobile learning in ESP is scarce, despite its importance in sustaining education. Thus, this review systematically identifies the trends of mobile learning concerning ESP. Using three databases, namely Web of Science (WoS), Scopus, and Educational Resources Information Centre (ERIC), 28 articles were extracted out of 139… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 56 publications
1
42
0
Order By: Relevance
“…Online learning has become a norm, which education globally should embrace (Rafiq et al, 2021). However, the United Nations Educational Scientific and Cultural Organisation (UNESCO) reported that online education lacks quality because teachers are unprepared for online pedagogical knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Online learning has become a norm, which education globally should embrace (Rafiq et al, 2021). However, the United Nations Educational Scientific and Cultural Organisation (UNESCO) reported that online education lacks quality because teachers are unprepared for online pedagogical knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…In enhancement, app development via HCI could embed the social constructivism theory by Vygotsky ( 1997 ) to include a teacher's role to scaffold language learning. Regardless, technological elements, such as audio–visual materials are preferred by learners as supported by other studies as well (Hashim, 2018 ; Rafiq et al, 2021 ). However, media or tools should not replace teachers' role as teachers who scaffold learning will give a better outcome for learners (Nasr et al, 2020 ).…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, it needs a novel solution from the perspective of HCI. Almost everyone owns a mobile device, which means a mobile application can create supplementary lessons for STEM learners as a new advanced platform for learning (Klimova and Pikhart, 2021 ; Rafiq et al, 2021 ). Hence, this study aims to explore the needs of STEM learners in creating the English language competency mobile module.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile learning also ensures quality education for all by availing opportunities for everyone to learn about new concepts and acquire knowledge about ESD [46]. Since this generation is more accustomed to mobile technologies, as evidenced in their everyday life [47], involving technologies, such as mobile learning or flipped classroom or interactive game-based learning [48] employing mobile technologies to facilitate RE-centered ESD would much more efficiently and effectively encourage this generation of students to pursue the curricula. Apart from the traditional formal learning approach, another educational strategy that could be proposed for RE-targeted ESD from this analysis is the non-formal learning approach in which external sources, such as the media, society, and external personnel links, can be employed to help the students acquire knowledge and awareness regarding RE and ESD [36].…”
Section: Discussionmentioning
confidence: 99%